2013
DOI: 10.4025/actascitechnol.v35i2.14775
|View full text |Cite
|
Sign up to set email alerts
|

High performance controller for drying processes

Abstract: ABSTRACT. This paper proposes a high performance nonlinear fuzzy multi-input-multi-output controller for a drying control process. The highly nonlinear characteristics of drying processes make classical control theory unable to provide the same performance results as it does in more well behaved systems. Advanced control strategies may be used to design temperature, relative humidity and air velocity nonlinear tracking controllers to overcome its highly non-linear dynamics over the whole drying operating condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Currently, there are many control techniques used for the food drying system such as herb [5], gain [6], codfish [7][8], and fruit [9]. Nafeh et al [5] investigated a temperature control in a PV-Wind medical herb dryer system by using on/off controller that showed the high capability of the proposed technique in controlling the drying temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are many control techniques used for the food drying system such as herb [5], gain [6], codfish [7][8], and fruit [9]. Nafeh et al [5] investigated a temperature control in a PV-Wind medical herb dryer system by using on/off controller that showed the high capability of the proposed technique in controlling the drying temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [6] used a model predictive control (MPC) system based on neural network which was designed and tested on two model corn dryers that the control method of the system can be used in drying process control. Boeri et al experimentally investigated the optimized operating drying control for temperature, relative humidity and air velocity parameters by using fuzzy logic approach [7] and also proposed the multiinput-multi-output-based PID and Fuzzy logic (FLC) controller for a drying control process [8]. Geddes [9] implemented an internal model control (IMC) model to the temperature controller for fruit dryer process in which the simulation results showed that IMC controlled system could achieve the requirement of providing offset-free responses at steady state.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, temperature and air velocity are factors affecting water removal rate during food drying (Boeri et al, 2013). Therefore, the control of these factors is very important in drying, as the desired moisture content of the food will be achieved if the temperature and air velocity are appropriate.…”
Section: Introductionmentioning
confidence: 99%